Gyrification Connectomes in Unmedicated Patients With Schizophrenia and Following a Short Course of Antipsychotic Drug Treatment - Nelson, Eric A.; White, David M.; Kraguljac, Nina V.; Lahti, Adrienne C. (Frontiers in Psychiatry, 2018)
Schizophrenia (SZ) is a disease characterized by brain dysconnectivity and abnormal brain development. The study of cortical gyrification in schizophrenia may capture underlying alterations reflective of neurodevelopmental abnormalities better than other imaging modalities. Graph-based connectomic approaches have been previously used in schizophrenia to study structural and functional brain covariance using a diversity of techniques. The goal of the present study was to evaluate morphological covariance using a measure of local gyrification index in patients with schizophrenia. The aims of this study were twofold: (1) Evaluate, in unmedicated SZ, the structural covariance of local gyrification index using graph theory measures of integration and segregation, and (2) investigate the effect of a short antipsychotic drug (APD) treatment on these measures. Using a longitudinal prospective design, structural scans were obtained prior to treatment in 34 unmedicated patients with SZ and after 6 weeks of treatment with risperidone. To control for the effect of time, 23 matched healthy controls (HC) were also scanned twice, 6 weeks apart. The cortical surface of each structural image was reconstructed and local gyrification index values were computed using FreeSurfer. Local gyrification index values where then parcellated into atlas based regions and entered into a 68 × 68 correlation matrix to construct local gyrification index connectomes for each group at each time point. Longitudinal comparisons showed significant group by time interactions for measures of segregation (clustering, local efficiency) and modularity, but not for measures of integration (path length, global efficiency). Post hoc tests showed increased clustering, local efficiency, and modularity connectomes in unmedicated patients with SZ compared to HC. After 6 weeks of treatment, there were no significant differences between the groups on these measures Abnormal cortical topography is detected in schizophrenia, likely indexing neurodevelopmental trajectory deviations. In addition, cortical topography is modified by short term APD treatment reflective of decreases in hyper-specialization in network connectivity. We speculate that changes in the structural organization of the brain is achieved through the trophic effects that APDs have on brain tissue, thus promoting better brain connections and, possibly, a therapeutic effect.